Studi Inkompatibilitas Parenteral dan Penggunaan Antibiotika Pada Pasien Rawat Inap Di Rumah Sakit Surakarta - Avianti Dewi Purwaningsih; Lukito Mindi Cahyo (Fakultas Farmasi Universitas Setia Budi, 2018)
Intravenous admixtures is a process of admixtures sterile drugs with sterile intravenous solutions to produce a sterile preparation aimed at intravenous use. The scope of intravenous admixtures is to dissolve or reconstitute sterile powders, prepare simple intravenous injections, and prepare complex intravenous injections. Identification and evaluation of incompatibility events in the drug dispensing stage in the hospital aims to determine incompatibility events, know the prescription patterns of intravenous preparations, know the process of drug dispensing, determine the effect of pharmacist ability on incompatibility events, find out the incompatibility with outcome therapy, and incidence of incompatibility on antibiotic use. This research needs to be done because incompatibility is a high risk problem in a hospital. The study used experimental studies, namely to provide an understanding of the effect of quantitative incompatibility and observational studies to determine the incidence of antibiotic incompatibility. The samples used were inpatients in the hospital, excluding hemodialysis patients and labor patients. Data retrieval is done retrospectively, to obtain qualitative data and prospectively, to obtain quantitative data. The results of this study obtained the greatest antibiotic use was Ceftriaxone with NaCl solvents. Incompatibility occurring at 19.5% includes chemical and physics incompatibility. This study concluded that there was no significant relationship between the use of antibiotics and the incidence of incompatibility.